The Content of the Category “Supranationalism” in the Contemporary International Legal Doctrine - V. V. Gavrilov; V. E. Danshov (Московский журнал международного права)
INTRODUCTION. The increase in the number of interstate associations with an intrastate authority, delegated by State members is one of the main characteristics of contemporary world. In the international legal doctrine, the accepted term for such associations is supranational when the phenomenon of delegation and exercise the authority on interstate level is called supranationalism. Despite the fact that official documents and research works consist the term under consideration in the middle of 20th century, so far, the complex and generally accepted definition of supranationalism has not been formed. This situation negatively effects on correct understanding the essence and prospects for the development of integrational processes taking place in modern international relations. This article seeks to overcome this uncertainty.MATERIALS AND METHODS. When writing the work, a number of theoretical studies of domestic and foreign international lawyers of the second half of the 20th – beginning of the 21st centuries, as well as legal sources that are important for revealing the research topic, were analyzed. During the research implementation, the authors used historical, comparative legal and some other general scientific and special legal methods.RESEARCH RELULTS. Within the framework of the work, it was substantiated the assertion that the content of supranationality, first of all, consists in endowing the bodies of an interstate association with certain domestic powers, which determines its close relationship with such a category of international law as “integration”. Subsequently, based on comparison of two definitions, it was justified that supranationalism can be considered as one of the methods for integration in interstate associations. At the same time, given that in this case, the transfer of domestic powers to the interstate level is being carried out, and supranationality implies close interaction between international and domestic law, the system of guarantees that ensure the stable development and integration of states within such associations is of particular importance.DISCUSSION AND CONCLUSION. The general conclusion of the article is that supranationalism should be understood as a way of organizing and operating an interstate association, which has a certain degree of independence and is vested with intrastate authority for the purpose of international legal integration of its member states, subject to a balance of domestic and international beginnings in the process of functioning of such an association.